The Effectiveness of Compassion-Focused Therapy on Negative Meta-Emotions and Sexual Self-Efficacy in Women Affected by Extramarital Relationships - Maghbareh , Parisa; Mardani, Parisa; Faghih Tabaghdehi, Alireza (Psychology of Woman Journal, 2025)
Objective: This study aimed to investigate the effectiveness of Compassion-Focused Therapy (CFT) in reducing negative meta-emotions and enhancing sexual self-efficacy in women affected by extramarital relationships.Methods and Materials: The study employed a randomized controlled trial design with pre-test and post-test assessments and no follow-up. A total of 60 married women aged 25–40 years who had experienced psychological distress due to their spouse's extramarital relationship were selected from counseling centers in Tehran. Participants were randomly assigned to an intervention group (n = 30) receiving eight weekly 90-minute sessions of CFT, and a control group (n = 30) receiving no psychological intervention. Data were collected using the Meta-Emotion Scale (MES) and the Sexual Self-Efficacy Scale – Female Functioning (SSES-F). Statistical analyses were conducted using ANCOVA and Bonferroni post-hoc tests via SPSS-27.Findings: The ANCOVA results indicated significant differences between the groups in both outcome variables after controlling for pre-test scores. For negative meta-emotions, the intervention group showed a substantial decrease compared to the control group (F(1, 56) = 91.63, p < .001, η² = .611). Similarly, sexual self-efficacy significantly increased in the intervention group compared to the control (F(1, 56) = 68.51, p < .001, η² = .550). These results confirm the efficacy of CFT in improving both emotional and sexual functioning in the target population.Conclusion: Compassion-Focused Therapy is an effective intervention for reducing negative meta-emotions and enhancing sexual self-efficacy in women experiencing emotional trauma from extramarital betrayal. Integrating compassion-based strategies may be critical in therapeutic programs aimed at post-betrayal recovery.